Gauss-Radau Small-body Simulator (GRSS): An Open-source Library for Planetary Defense - Rahil Makadia; Davide Farnocchia; Steven R. Chesley; Siegfried Eggl (The Planetary Science Journal)
We present GRSS , a small-body propagation and orbit determination library specifically designed for planetary defense applications. GRSS is an end-to-end, open-source software tool that begins with optical observations obtained from the Minor Planet Center and Gaia spacecraft, as well as radar observations from the Jet Propulsion Laboratory, and ends with reliable predictions about the trajectory of a small body in the solar system. The library is built on a C++11 orbit propagation core and provides additional orbit determination capability through a Python interface for ease of use. We conducted extensive validation for both of these components of the library by comparing them with the state-of-the-art operational software tools. We demonstrate the capabilities of GRSS by applying it to orbit propagation for (65803) Didymos and orbit determination for (29075) 1950 DA. We also used GRSS to calculate the keyholes for the 2135 close encounter of (101955) Bennu and determine the impact location for 2024 BX _1 and 2024 RW _1 . The library is designed to be modular and extensible, allowing for future addition of additional orbit filters and dynamical models. GRSS is publicly available on GitHub under a GPLv3 license and is intended to be a community resource for planetary science and planetary defense.